(untitled) (The Review of Diabetic Studies, 2025)
Background: IC and HAI are two important areas in the field of patient/healthcare worker safety that have been the cornerstone with which the challenges are continually raised in renewed attention and renewed focus. The formation of effective IPC programs is a task that is not only the domain of a particular sector but also the collective awareness, attitudes, and practices by a diversified group of professionals. The systematic analysis in the following study will examine a closer analysis of the IC capability of six groups of professionals. These include nursing professionals, emergency care workers in the ED department, radiologic imaging technicians, dental health care workers (DHCWs), pharmacy assistants, and laboratory workers. Methods: The six groups of professionals have been studied using a set of descriptive and observational studies that have been carried out in the time frame 2019-2025, with geographical distribution in Kenya, Kingdom of Saudi Arabia, and Egypt. The trend analysis suggests a disturbing consensus among the six groups of professionals regarding the mismatch in awareness and the practicality in the everyday approach to IC. The analysis also suggests some areas in which the approaches are poor. Results: Such common drivers include the fluctuating nature of training/education in an endless stream of continuous competence; physical and policy resource deficits; and the absence of adequate means of communication between the departments. This review contends that in order to overcome the aforementioned deficiencies, there has to be a paradigm shift in the form of an IC strategy that is multidisciplinary in its chosen approach. This will have to include competency training tailored to specific roles; strict policy implementation, including standard compliance and ‘auditability’ across the board in every department; the use of health informatics in real-time monitoring and communication; and the promotion of an institutional ‘safety culture.’ Conclusion: This article provides an outline of an effective approach to the gamut of infection prevention, as it were, in the form of a comparative outline in the tables presented above. The article’s main intention in this regard has been to offer an evidence-based framework regarding the nature of an effective IC strategy in order to contribute toward the improvement of the current paradigm.